Factors Influencing Consumer Purchase Intention on Malaysian Cuisine among Urbanites in Chengdu City - Hee, Ong Choon; Hee, Chan Uri; Kowang, Tan Owee; Fei, Goh Chin; Char Fei, Theresa Ho; Husin, Maizaitulaidawati Md; Ping, Lim Lee (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to investigate factors that influence consumer purchase intention on Malaysian cuisine among urbanites in ChengDu, China. ChengDu is one of the biggest cities located at the South West of China and well-known of its local spicy cuisine. To date, there is no study conducted in ChengDu in relation to purchase intention on Malaysian cuisine. Hence, this study intends to fill the gap by using perceived price, service quality, brand image and advertisement to be tested with consumer purchase intention. Convenience sampling method was used in this study with self-administered survey questionnaire which yielded 400 responses. The findings revealed that all factors were significantly associated with consumer purchase intention. This research is expected to provide important information, recommendations and marketing strategies to Malaysian cuisine restaurant owners in ChengDu city. It also contributes to the related body of knowledge and stimulating further research especially in the area of cross-border marketing study.